Pengaruh Pertumbuhan Ekonomi, Pendidikan dan Kesehatan Terhadap Tingkat Kemiskinan Di Indonesia Pada Tahun 2013-2022 - Rokhimah imah; Fatima Az-zahra Wairooy; Nila Amanda Dinilah; Siti Fatimah Azzahra (Prodi Ekonomi Syariah IAIN Sorong, 2024)
This study focuses on the analysis of the effect of economic growth, education, and health on poverty rates in Indonesia during 2013-2022. The results showed that economic growth has a negative influence on poverty, meaning that faster economic growth does not directly reduce poverty. Education, by contrast, has a positive influence on poverty, with greater educational improvements reducing poverty. Health, in this study, did not have a significant effect on poverty, meaning that health did not play a role in reducing poverty. The conclusion of this study shows that poverty reduction strategies in Indonesia should focus on improving education and developing social programs that are more effective in reducing poverty, as well as paying attention to broader health aspects. Thus, this research contributes to the development of more effective strategies in reducing poverty in Indonesia.